Comparison of Post-Operative Astigmatism Followed by Extracapsular Cataract Extraction (ECCE) Surgical Procedure Demographically (Medical Forum Monthly, 2021)
Objective: To compare post-operative astigmatism demographically between continuous and interrupted sutures in patients undergoing ECCE surgery.Study Design: Longitudinal studyPlace and Duration of Study: This study was a multicenter study conducted from March 2019 to September 2020.Materials and Methods: 314 patients meeting the inclusion criteria were selected for the study and divided into two groups. In both the groups ECCE surgery was to be performed. Group A was to receive Limbal interrupted sutures, while group B Limbal continuous sutures. Astigmatism was recorded through keratometry and final outcomes were evaluated after 6 weeks. Data was analyzed using SPSS. Two groups were compared using Chi-square test, with level of significance being P-value ≤0.05.Results: 314 patients fulfilling the inclusion criteria were included in this study. The mean ± standard deviation age of study population was 60.55± 6.612 years. No significant difference was seen between the group of continuous and interrupted sutures in terms of astigmatism (P=0.32), but the patients undergoing continuous suturing technique had more astigmatism. Astigmatism was found to be significant for males (P=0.018) and age less than 50 years (P ≤0.00).Conclusion: There is no difference in the amount of Post-operative astigmatism between continuous and interrupted suture technique, male gender and age group less than 50 is more predisposed to astigmatism after ECCE